Educação financeira nos anos iniciais: concepções na literatura científica brasileira - CARDOSO, Débora Nogueira (2020)
This paper has as its theme the importance of financial education in the early grades. The method adopted in the formulation of this work is in agreement with the study proposal, which is adequate through the objectives to be achieved. The development of science is based on the achievement of results that allows validating hypotheses about a given event or fact, present or not in our lives. the present paper leaves the theme open, proposing that in the future a new research will be carried out, with the purpose of contextualizing the themes addressed here.